Gambaran Penguatan Profil Pelajar Pancasila pada SMP Negeri 2 Kota Jambi - Syahwal Alan; Siti Amanah; Rully Andi Yaksa (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
The role of Guidance and Counseling Teachers in strengthening the profile of Pancasila students in schools is very strategic. The implementation of guidance and counseling services in schools with the independent learning curriculum requires service components that are accompanied by plans and implementations that have been integrated with strengthening the profile of Pancasila students. Quantitative research type with descriptive methods. Descriptive research is a study that tries to answer existing problems based on data. The population in this study were all classes VIII A to VIII F with a total of 265 students. The results of the study showed that the profile of Pancasila students at SMP Negeri 002 Jambi City was 83.33 or a good category. The description of the dimensions of faith, devotion to God Almighty, and noble character in the profile of Pancasila students at SMP Negeri 002 Jambi City was 84.64% or a good category. The description of the global diversity dimension in the profile of Pancasila students at SMP Negeri 002 Jambi City was 87.09% or a good category. The description of the mutual cooperation dimension in the profile of Pancasila students at SMP Negeri 002 Jambi City is 84.12% or a good category. The description of the independent dimension in the profile of Pancasila students at SMP Negeri 002 Jambi City is 75.79% or a good category. The description of the critical reasoning dimension in the profile of Pancasila students at SMP Negeri 002 Jambi City is 82.71% or a good category. The description of the creative dimension in the profile of Pancasila students at SMP Negeri 002 Jambi City is 83.33% or a good category.